2020
DOI: 10.3390/w12051327
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Patterns of Changes in River Water Temperature in Poland

Abstract: The study determined water temperature trends of rivers in Poland in the period 1971–2015, and also their spatial and temporal patterns. The analysis covered daily water temperature of 53 rivers recorded at 94 water gauge stations and air temperature at 43 meteorological stations. Average monthly, annual, seasonal and maximum annual tendencies of temperature change were calculated using the Mann–Kendall (M–K) test. Regional patterns of water temperature change were determined on the basis of Ward’s hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 57 publications
3
26
0
Order By: Relevance
“…The majority of authors have focused on an assessment of change tendencies at the start and end dates of RI and its duration, which, in light of the recorded increase in TA and TW, usually gives a result pointing to the shortening thereof. Apart from warmer winters, an increase in TA in the autumn and spring periods has also been noticeable, especially during the last twenty years of the 20th century but in recent decades as well [38,39,[69][70][71][72], which delays the date of appearance of IP in rivers and also accelerates their disappearance. Analyses conducted for the last five-to-six decades in Polish rivers [21,22,24,25,31,42,51,64,65,[73][74][75] have confirmed that the duration of IP has been shortened, though their respective change trends have differed along individual river sections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of authors have focused on an assessment of change tendencies at the start and end dates of RI and its duration, which, in light of the recorded increase in TA and TW, usually gives a result pointing to the shortening thereof. Apart from warmer winters, an increase in TA in the autumn and spring periods has also been noticeable, especially during the last twenty years of the 20th century but in recent decades as well [38,39,[69][70][71][72], which delays the date of appearance of IP in rivers and also accelerates their disappearance. Analyses conducted for the last five-to-six decades in Polish rivers [21,22,24,25,31,42,51,64,65,[73][74][75] have confirmed that the duration of IP has been shortened, though their respective change trends have differed along individual river sections.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of circulatory determinants impacting the occurrence of IC in the Noteć River was performed by Graf and Tomczyk [23], while an assessment of the relationship between the TW of Polish rivers and large-scale atmospheric circulation, which was accompanied by the disclosure of TW change patterns in Poland, was carried out by Graf and Wrzesiński [38,39] and Marszelewski and Pius [71,72]. Research conducted by Yoo and D'Odorico [5] in Northern Europe showed that the ice regime of surface waters is connected with changes in the North Atlantic Oscillation (NAO) index, the features of which confirm long-term climate change [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last 70 years, sewage water discharged to the Ner has changed, both quantitatively and qualitatively. This was due to various processes and phenomena associated with the increase in population of the entire Lodz agglomeration, its economic and industrial development, changes in local water management, and river water temperature changes due to the warming climate (Graf, & Wrzesiński 2020). All of these caused long-term fluctuations and periodic trends in the quantity of sewage discharged into the river from the Lodz agglomeration, as well as similar changes in the degree of its biochemical, chemical and thermal pollution (only since 1995 has this wastewater been biologically treated in CWTP LA).…”
Section: Characteristics Of the Ner Rivermentioning
confidence: 99%